H. L. Mencken papers - Mencken, H. L. (Henry Louis), 1880-1956.
Correspondence (1927-1941, undated) and signed typescript of Mencken's diary (1917) written while serving as a correspondent for the Baltimore Sun. Documents events surrounding the break in diplomatic relations between the U.S. and Germany. Also includes accounts of conversations and travels with the U.S. ambassador to Germany, James Watson Gerard; travels through Switzerland, France, and Spain; and a voyage from Spain to Havana, Cuba.
In part, photocopies.
Author and editor.
Collection material in English.
Keywords: Gerard, James W. -- 1867-1951.; Sun (Baltimore, Md. : 1837); American newspapers -- Maryland -- Baltimore; World War, 1914-1918 -- Journalists; World War, 1914-1918 -- Germany; Cuba -- Description and travel; France -- Description and travel; Germany -- Description and travel; Germany -- Foreign relations -- United States; Havana (Cuba) -- Description and travel; Spain -- Description and travel; Switzerland -- Description and travel; United States -- Foreign relations -- Germany; Authors; Editors